Research advances on Golgi stress response in bone metabolism - NIU Pingping; SUN Yao (Kouqiang hemian waike zazhi)
During the growth, development, and injury repair processes of mammals, organelles undergo self-regulation through a series of complex regulatory mechanisms when subjected to interference from inside or outside, in order to maintain cellular homeostasis. This process is known as organelle stress response. The Golgi apparatus is a key organelle within the cell, not only participating in physiological activities such as the processing and modification of intracellular proteins, lipid metabolism, and vesicular transport, but also playing an important role in ion homeostasis and stress responses. Bone metabolism is an important and complex process for maintaining skeletal health, involving the coordinated action of various cells such as osteoblasts and osteoclasts. In this process, the stress response of the Golgi apparatus helps to maintain the intracellular homeostasis and physiological functions of bone cells. This article reviews the research progress on Golgi apparatus stress response, including its structure, function, triggering factors, signal transduction pathways, and its impact on the function of bone tissue cells, aiming to provide new insights for the treatment of bone diseases.